2022
DOI: 10.1093/gbe/evac123
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Phylogenomics of Methylobacterium Reveals Four Evolutionary Distinct Groups and Underappreciated Phyllosphere Diversity

Abstract: Methylobacterium is a group of methylotrophic microbes associated with soil, fresh water, and particularly the phyllosphere, the aerial part of plants that has been well-studied in terms of physiology but whose evolutionary history and taxonomy are unclear. Recent work has suggested that Methylobacterium is much more diverse than thought previously, questioning its status as an ecologically and phylogenetically coherent taxonomic genus. However, taxonomic and evolutionary studies of Methylobacterium have mostl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Using NCBI BLAST, rpoB sequences from each isolate were compared against the Joint Genome Institute’s (JGI) Integrated Microbial Genomes (IMG) database to putatively assign species-level taxonomic classifications to each isolate. All isolates matched to Methylobacterium species within group B (24) , with the closest species being Methylobacterium extorquens AM1, Methylobacterium extorquens PA1, Methylobacterium extorquens TK001, and Methylobacterium zatmanii 135. Untrimmed rpoB sequences from each isolate, as well as from reference Methylobacterium and related species, were aligned using MUSCLE, and Maximum-Likelihood trees with 100 bootstrap replications were constructed using MEGA ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Using NCBI BLAST, rpoB sequences from each isolate were compared against the Joint Genome Institute’s (JGI) Integrated Microbial Genomes (IMG) database to putatively assign species-level taxonomic classifications to each isolate. All isolates matched to Methylobacterium species within group B (24) , with the closest species being Methylobacterium extorquens AM1, Methylobacterium extorquens PA1, Methylobacterium extorquens TK001, and Methylobacterium zatmanii 135. Untrimmed rpoB sequences from each isolate, as well as from reference Methylobacterium and related species, were aligned using MUSCLE, and Maximum-Likelihood trees with 100 bootstrap replications were constructed using MEGA ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 93%
“…Yet, studies investigating the physiology, biodiversity, and ecology of methylotrophic communities of the phyllosphere have only emerged within the last decade (3,31) and do not take into account the role of lanthanides in influencing their community composition. Furthermore, despite the abundance of methylotrophs in the phyllosphere, the bulk of phylogenomic studies on Methylobacterium species use genomes isolated from non-phyllosphere environments (24). Here, we describe the first community-level characterization of the role of lanthanides during the metabolisms of natural methylotrophic populations in soybean plants, revealing novel insights into methylotrophic biodiversity, metabolic capabilities, and lanthanide-dependent metabolisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9.3 . We discussed a recent paper [6], in which the authors suggested that Methylobacterium sensu lato could be split into four distinct genera, based on different genome characteristics (gene content, core genome architecture, G+C content, genome size). The study confirms that the clade containing the ‘symbiotic’ species (rhizobial species; e.g.…”
Section: Minute 9 Recent Relevant Publications In Taxonomymentioning
confidence: 99%
“…As a potential solution to mitigate Rare Earth Element (REE) pollution, several methylotrophic bacteria have been shown to uptake and store light lanthanides and are being proposed as a potential tool for bioremediation and biomining[14, 15]. Furthermore, we have recently developed a mutant of Methylobacterium [16]/ Methylorubrum extorquens AM1 that has acquired the ability of hyperaccumulating heavy lanthanides such as gadolinium [17] . The methylotrophic bacteria express a unique protein with the ability to bind lanthanides with picomolar affinity, termed lanmodulin[18, 19].…”
Section: Introductionmentioning
confidence: 99%